The effect of mastication on memory loss : Pengaruh mastikasi terhadap penurunan daya ingat - Irsal Wahyudi Sam; Bahruddin Thalib (Makassar Dental Journal PDGI Makassar, 2021)
Mastication has a long-term effect on the central nervous system and helps prevent degradation of brain function. Mastication is a complicated movement that results from a group of nerves in the brain stem and nerve tissue that involves several regions in the brain. Recent research suggests that there is a relationship between mastication, age, and decreased cognitive function in humans. Reduced masticatory activity, a risk factor for developing memory loss in humans, weakens spatial memory and causes neurons in the hippocampus to deteriorate morphologically and functionally. This often occurs in people with advanced age, where usually at an advanced age there will be changes in the oral cavity, such as tooth loss which can reduce the function of mastication in elderly people, causing them to experience decreased brain function. The purpose of this literary review is to evaluate the effect of mastication on alzheimer's.